2016
DOI: 10.1155/2016/5893481
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of Long Noncoding RNAs in Human Earlobe Keloids: A Microarray Analysis

Abstract: Background. Long noncoding RNAs (lncRNAs) play key roles in a wide range of biological processes and their deregulation results in human disease, including keloids. Earlobe keloid is a type of pathological skin scar, and the molecular pathogenesis of this disease remains largely unknown. Methods. In this study, microarray analysis was used to determine the expression profiles of lncRNAs and mRNAs between 3 pairs of earlobe keloid and normal specimens. Gene Ontology (GO) categories and Kyoto Encyclopedia of Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Once the basic knowledge of the lncRNA was recognized, its application followed. For application studies, the lncRNA has the potential for diagnosis as a biomarker [ 29 ]. It was recommended that lncRNA might be a treatment target in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Once the basic knowledge of the lncRNA was recognized, its application followed. For application studies, the lncRNA has the potential for diagnosis as a biomarker [ 29 ]. It was recommended that lncRNA might be a treatment target in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray profiling of long noncoding RNAs (lncRNAs) has also been performed in lesional keloid tissue, identifying altered expression of CACNA1G-AS1 and HNF1A-AS1, which interact not only with pro-fibrotic TGF-β pathways, but also with cellular adhesion and tight junction signaling [ 40 , 41 ]. Another study reported altered expressions of 30 lncRNAs relating to hedgehog signaling pathways, which were accompanied by mRNA changes reflecting upregulation of cell proliferation and tissue repair and downregulation of apoptotic pathways in keloid tissue [ 42 ].…”
Section: Fibrosing Disorders Of the Skinmentioning
confidence: 99%
“…More and more studies showed that lncRNAs play an important role in different biological processes, such as cell growth, proliferation, and apoptosis [7]. It has been proposed that plenty of lncRNAs were closely related to the progression of keloid fibrosis [8], such as HNF1A-AS1 [9], COL1A2-AS1 [10], CACNA1G-AS1, HOXA11-AS, LINC00312, and RP11-91I11.1 [11]. Recent study demonstrated that calcium voltage-gated channel subunit alpha1 G antisense RNA 1 (CACNA1G-AS1) was up-regulated in keloid and had a positive effect on cell migration in keloid fibrosis [12].…”
Section: Introductionmentioning
confidence: 99%